Terminal group effects of DOPO-conjugated flame retardant on polyamide 6: Thermal stability, flame retardancy and mechanical performances - Gao, Jing; He, Wentao; Xiang, Yushu; Long, Lijuan; Qin, Shuhao (Frontiers in Chemistry, 2022)
Two DOPO-conjugated flame retardants with or without amino terminal groups (DOPO-NH2 and DIDOPO, respectively) were synthesized and incorporated into polyamide 6 (PA6). Results demonstrated the DOPO-NH2 endowed superior thermal, flame retardant and mechanical performances to PA6 composites. With the same loading of 15wt%, DOPO-NH2 can catalyze the PA6 matrix more effectively and result in more residues in high temperature. The PA6 composites containing DOPO-NH2 exhibited higher LOI (28.0%) compared to 25.0% for the sample containing DIDOPO, and brought the lower heat release capacity and peak heat release rate. Furthermore, the overall mechanical properties of PA6 composites containing DOPO-NH2 outperformed the samples containing DIDOPO, even superior to that for PA6. Such a significant difference can be mainly attributed to the existence of amino-terminal group, which can interact with carboxyl group in PA6 as confirmed by dynamic mechanical analysis, improving the compatibility between the flame retardant and PA6 matrix.